Philometra mirabilis sp. n. (Nematoda: Philometridae), a new gonad-infecting parasite from the freshwater fish Cichla mirianae (Cichlidae) in Brazilian Amazon - Moravec, František; Diggles, Ben (Parasitology research, 2015)
A new nematode species, Philometra mirabilis sp. n. (Philometridae), is described based on a subgravid female specimen recovered from the ovary of the freshwater perciform fish Cichla mirianae Kullander and Ferreira (Cichlidae) in the Juruena River (Amazon River basin), State of Mato Grosso, Brazil. The new species is morphologically very different from congeners parasitizing fishes in South America, being mainly characterized by the markedly elongate, narrow body 171 mm long (maximum width/body length 1:598), the presence of three small cone-shaped oesophageal teeth protruding out of the mouth and an onion-shaped oesophageal inflation distinctly separated from the posterior part of the oesophagus, the relative length of the oesophagus, and the rounded posterior end of the body without any caudal projections. It is the third known valid species of Philometra Costa, 1845 parasitizing a freshwater fish in South America and the second species of this genus reported from fishes of the family Cichlidae.
Keywords: hlístice; Fish Diseases; Cichlids; Brazil; Nematoda; řeky; Rivers; Brazílie; cichlidy; Animals; lidé; ženské pohlaví; Humans; nematodózy; zvířata; nemoci ryb; Ovary; Nematode Infections; Female; ovarium